THE SPECTRUM OF BACTERIAL AGENTS ISOLATED FROM THE WOUND IN PATIENTS WITH DIABETIC FOOT SYNDROME IN ONE OF THE HOSPITALS IN CHELYABINSK - N. M. SHLEPOTINA; O. L. KOLESNIKOV; L. L. PLOTKIN; YU. S. SHISHKOVA (Кубанский научный медицинский вестник, 2018)
Aim. To establish the features of the spectrum and antibiotic resistance of bacterial agents isolated from wounds in patients with diabetic foot syndrome.Materials and methods. In 2016-2017 a retrospective cohort study was carried out on the basis of the archive of the municipal budgetary healthcare institution «City clinical hospital №6» in Chelyabinsk with analyzing the data of the medical cards of patients who were at the department of purulent surgery in 2015 with various forms of diabetic foot syndrome. The main data for the study were taken from the results of bacteriological studies. To determine the antibiotic susceptibility of the isolated flora, a diffusion method was used with discs with antibiotics. The classification proposed by Wagner F.W. was used to determine the prevalence and depth of the lesion of diabetic foot syndrome (1979). The statistical processing of data was carried out using Excel 12.0 (Office 2008), the level of significance of the results was evaluated by calculating the two-sided exact Fisher test (F) using the calculator on the site «Medical Statistics» (URL: http://medstatistic.ru/calculators/calchi.html).Results. In the studied group of patients with diabetic foot syndrome the infectious process caused by one bacterial agent was most often encountered. The most common causative agent isolated from the wound defects was S. aureus. The tendency to develop resistance against antibiotics, widely used in clinical practice, is more pronounced in representatives of gram-negative flora.Conclusion. The obtained data generally coincide with the results of studies in the field of the microbial spectrum of the wounds in diabetic foot syndrome determined by other authors, but the predominance of monoinfections over bacterial associations in this studied population requires further study.